Chronic (52-week) oral toxicity study of herbal tea of Moringa stenopetala and Mentha spicata leaves formulation in Wistar albino rats - Abdu Hassen Musa; Girmai Gebru; Asfaw Debella; Eyasu Makonnen; Mesfin Asefa; Samuel Woldekidan; Boki Lengiso; Chala Bashea (International Journal of Pharmaceutical Sciences and Developmental Research - Peertechz Publications, 2022)
Background: Moringa stenopetala leaves have long been used to treat diabetes, hypertension, respiratory problems, and other diseases. The herbal formulation of Moringa stenopetala and Mentha spicata leaves was found to be more effective in lowering high blood pressure and blood sugar levels. Unlike its pharmacological properties, the long-term safety profile of this herbal formulation has not been investigated yet. Thus, this study investigated the long-term (chronic) oral toxicity of herbal tea of M. stenopetala and M. spicata leaves blended in rats.  Methods: Wistar albino rats were randomly distributed into four groups (n = 10/sex/group), and then randomly assigned to a control group and three test groups. The control group (G I) received distilled water. The test groups (G II-IV) received 559.36, 1118.72, and 2237.44 mg/kg of herbal tea of M. stenopetala and M. spicata leaves blend respectively, for 360 consecutive days. During the treatment period, in-life parameters (mortality, clinical symptoms, body weight, and food intake) were evaluated. On the 361st day, hematological, serum biochemical, gross morphological, and histological parameters were investigated. Results: Throughout the 360-day treatment period, no herbal tea-related deaths, severe clinical symptoms, loss of body weight, or food intake were seen in any of the treated groups. Bodyweight, food consumption, organ weight, hematological, and serum biochemical findings showed no significant differences between the control and treated groups in both sexes. Macro-pathological and histopathological examinations of the major organs (liver, kidney, heart, pancreas, stomach, and spleen) revealed no herbal tea-related pathologic alterations.  Conclusion: The findings indicate that long-term (360-days) oral administration of the herbal tea of M. stenopetala and M. spicata leaves blend is well tolerated by rats. Hence, it would be safe/low toxic up to a dose of 2237.44 mg/kg/day in chronic exposure.